2021
DOI: 10.3389/fphar.2021.687360
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Cholesterol Modulates the Interaction Between 17-βEstradiol and the BK Channel

Abstract: BK channels are composed by the pore forming α subunit and, in some tissues, is associated with different accessory β subunits. These proteins modify the biophysical properties of the channel, amplifying the range of BK channel activation according to the physiological context. In the vascular cells, the pore forming BKα subunit is expressed with the β1 subunit, where they play an essential role in the modulation of arterial tone and blood pressure. In eukaryotes, cholesterol is a structural lipid of the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Recently, we reported that changes in cholesterol concentration reduces the effects of 17β-Estradiol (E2) in the BK channel activity. However, that effect was not induced by changes in the expression of the BK β1 subunit ( Granados et al, 2021 ). Considering that hypoxia reduces the membrane cholesterol concentration, we suggested that reported changes in the modulation of Tamoxifen and E2 after hypoxia could also be related to changes in membrane cholesterol concentration.…”
Section: Bk Channel Modulation In Hypoxiamentioning
confidence: 99%
“…Recently, we reported that changes in cholesterol concentration reduces the effects of 17β-Estradiol (E2) in the BK channel activity. However, that effect was not induced by changes in the expression of the BK β1 subunit ( Granados et al, 2021 ). Considering that hypoxia reduces the membrane cholesterol concentration, we suggested that reported changes in the modulation of Tamoxifen and E2 after hypoxia could also be related to changes in membrane cholesterol concentration.…”
Section: Bk Channel Modulation In Hypoxiamentioning
confidence: 99%